Making decisions about treatment for young people diagnosed with depressive disorders: a qualitative study of clinicians’ experiences - Simmons, Magenta B (BioMed Central, 2013)
BACKGROUND: The imperative to provide effective treatment for young people diagnosed with depressive disorders is complicated by several factors including the unclear effectiveness of treatment options. Within this context, little is known about how treatment decisions are made for this population. METHODS: In order to explore the experiences and beliefs of clinicians about treatment decision making for this population, semi-structured, qualitative interviews were conducted with 22 psychiatrists, general practitioners and allied health professionals from health care settings including specialist mental health services and primary health care. Interviews were audio taped, transcribed verbatim and analysed using thematic analysis. RESULTS: Clinicians largely reported and endorsed a collaborative model of treatment decision making for youth depression, although several exceptions to this approach were also described (e.g. when risk issues were present), highlighting a need to adapt the decision-making style to the characteristics and needs of the client. A differentiation was made between the decision-making processes (e.g. sharing of information) and who makes the decision. Caregiver involvement was seen as optional, especially in situations where no caregivers were involved, but ideal and useful if the caregivers were supportive. Gaps between the type and amount of information clinicians wanted to give their clients and what they actually gave them were reported (e.g. having fact sheets on hand). A broad range of barriers to involving clients and caregivers in decision-making processes were described relating to four levels (client and caregiver, clinician, service and broader levels) and suggestions were given to help overcome these barriers, including up-to-date, accessible and relevant information. CONCLUSIONS: The current data support a collaborative model of treatment decision making for youth depression which: 1) focuses on the decision-making processes rather than who actually makes the decision; 2) is flexible to the individual needs and characteristics of the client; and 3) where caregiver involvement is optional. Shared decision making interventions and the use of decision aids should be considered for this area.